PERKEMBANGAN TAFSIR AL-QUR’AN PADA MASA SAHABAT - Andi Miswar (Rihlah : Jurnal Sejarah dan Kebudayaan, 2016)
Interpretation  of al-Qur'an have grown during  Prophet life  and he is the first mufassir. After Rasulullah passed away the prophet companies  occupied the second interpretor. The first person interpreted  al-Qur'an after Rasul is Ali and  than Ibnu Abbas.  Al-Qur'an was interpreted by  prophet companieas by using sources such as Qur’an, prophet tradition,their own opinions (ijtihad) and  israiliyat stories ( though this was not  mentioned and not  allowed by the Prophet.). Meanwhile interpretation of Prophet directly come from Allah or passed by jibril or from himself,  difference ways of this two interpretation  are not far differences, but the quality of these  interpretations  is far more eminent. Generally, the form of interpretation applied by  prophet companies is called  al-Ma'tsur  interpretation which means that the interpretation is based on prophet interpretation, tradition and hisrory. This doesn’t mean the ra’yu or thought was not exluded but included. Precisely in certain condition, they used ideas called  interpretation method (ijtihadi). The methode of  interpretation used was  ijmali ( global), which means a brief and clear  interpretation of verses.